Structure and function of seamount ecosystems in the Cape Verde Region, Northeast Atlantic - Cruise No. 79/3 - September 24 - October 23, 2009 - Las Palmas/Spain - Mindelo/Cape Verde - Christiansen, Bernd; Brand, Tim; Büntzow, Marco; Busecke, Julius; Coelho, Rui; Correia, Sandra; Denda, Anneke; Diniz, Tania; Jung, Sarina; Kaufmann, Manfred; Kieneke, Alexander; Kiriakoulakis, Kostas; et al. (DFG-Senatskommission für Ozeanographie, 2011)
Cruise M79/3 aimed at physical, biogeochemical and biological sampling at and around seamounts in the Cape Verde region. These seamounts are important targets for the local fishery, but nearly nothing is known about their ecology. In order to gain an advanced understanding of the functioning of these ecosystems within their special hydrographic and biogeochemical setting, and in comparison to other seamounts in the NE Atlantic, the following studies were performed on the example of Senghor Seamount and an oceanic reference station: - Identification and description of the physical forcing factors at Senghor Seamounts. - Assessment of the origin, quality and dynamics of particulate organic material in the water column and in the superficial sediments at the seamount. - Description of aspects of biodiversity, zoogeography and ecology of the seamount: communities, faunal connections, trophic relationships, dynamics and productivity. - Adding to the classification of seamounts based on topography and habitat types. In addition, geological samples were obtained at two further seamounts and at a young volcano field south of Santo Antao. Complementing studies performed on cruise M81/1 and on the islands, they will further our understanding of the geological history of the area. : METEOR-Berichte